Impact of comprehensive molecular testing to reduce antibiotic use in community-acquired pneumonia (RADICAP): a randomised, controlled, phase IV clinical trial protocol. Issue 8 (20th August 2020) - Abelenda-Alonso, Gabriela; Rombauts, Alexander; Gudiol, Carlota; Meije, Yolanda; Clemente, Mercedes; Ortega, Lucía; Ardanuy, Carmen; Niubó, Jordi; Padullés, Ariadna; Videla, Sebastian; Tebe, Cristian; Carratalà, Jordi
Abstract : Introduction: Community-acquired pneumonia (CAP) continues to be a major health problem worldwide and is one of the main reasons for prescribing antibiotics. However, the causative agent is often not identified, resulting in antibiotic overtreatment, which is a key driver of antimicrobial resistance and adverse events. We aim to test the hypothesis that comprehensive molecular testing, compared with routine microbiological testing, would be effective in reducing antibiotic use in patients with CAP. Methods and analysis: We will perform a randomised, controlled, open-label clinical trial with two parallel groups (1:1) at two tertiary hospitals between 2020 and 2022. Non-severely immunosuppressed adults hospitalised for CAP will be considered eligible. Patients will be randomly assigned to receive either the experimental diagnosis (comprehensive molecular testing plus routine microbiological testing) or standard diagnosis (only microbiological routine testing). The primary endpoint will be antibiotic consumption measured as days of antibiotic therapy per 1000 patient-days. Secondary endpoints will be de-escalation to narrower antibiotic treatment, time to switch from intravenous to oral antibiotics, days to reaching an aetiological diagnosis, antibiotic-related side effects, length of stay, days to clinical stability, intensive care unit admission, days of mechanical ventilation, hospital readmission up to 30 days after randomisation and death from any cause by 48 hours and 30 days after randomisation. We will need to include 440 subjects to be able to reject the null hypothesis that both groups have equal days of antibiotic therapy per 1000 patient-days with a probability >0.8. Ethics and dissemination: Ethical approval has been obtained from the Ethics Committee of Bellvitge Hospital (AC028/19) and from the Spanish Medicines and Medical Devices Agency, and it is valid for all participating centres under existing Spanish legislation. Results will be presented at international meetings and will be made available to patients, their caregivers and funders. Trial registration number: ClinicalTrials: NCT04158492 . EudraCT: 2018-004880-29.